2000
DOI: 10.1016/s0016-5085(00)85400-1
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus GG prevents recurrence of colitis in HLA-B27 transgenic rats after antibiotic treatment

Abstract: Background and aims: Bacteroides vulgatus induces colitis in gnotobiotic HLA-B27 transgenic (TG) rats while broad spectrum antibiotics prevent and treat colitis in specific pathogen free (SPF) TG rats although disease recurs after treatment ends. Lactobacilli treat human pouchitis and experimental colitis. We investigated if Lactobacillus rhamnosus GG (L GG) can prevent colitis in TG rats monoassociated with B vulgatus and if L GG or Lactobacillus plantarum 299v (LP 299v) can treat established colitis in SPF T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(61 citation statements)
references
References 20 publications
(30 reference statements)
6
54
0
1
Order By: Relevance
“…Treatment with Lactobacilus sobrius prevented the increase of IL-8 and induced a strong upregulation of IL-10 ( Roselli et al 2007). These results are consistent with previous studies indicating that probiotics may reduce intestinal disorders through reduced IL-8 and increased IL-10 production (Ulisse et al 2001;Dieleman et al 2003;Otte et al 2004). Our findings of serum IL-10 level upregulation of piglets challenged with LPS was consistent with these previous studies.…”
Section: Immune Functionsupporting
confidence: 93%
“…Treatment with Lactobacilus sobrius prevented the increase of IL-8 and induced a strong upregulation of IL-10 ( Roselli et al 2007). These results are consistent with previous studies indicating that probiotics may reduce intestinal disorders through reduced IL-8 and increased IL-10 production (Ulisse et al 2001;Dieleman et al 2003;Otte et al 2004). Our findings of serum IL-10 level upregulation of piglets challenged with LPS was consistent with these previous studies.…”
Section: Immune Functionsupporting
confidence: 93%
“…The probiotic Lactobacillus rhamnosus GG and probiotic compound VSL#3 have previously been shown to reduce levels of MPO in the colitis setting [34] and prevent recurrence of colitis after antibiotic treatment [35], and the probiotic Bifidobacterium infantis has been shown to be effective in the treatment of irritable bowel syndrome [12]. At the doses tested, the probiotics investigated in the current study could not prevent the intestinal damage caused by administration of 5-FU.…”
Section: Discussionmentioning
confidence: 65%
“…However, a decrease in crypt cell apoptosis was observed following Bb12 administration compared to indomethacin alone. Previous studies have shown LGG to be beneficial in the treatment of inflammatory disorders of the GI tract [12,26,27]. However, a recent study by Moon et al [28] suggested that LGG actually increased the severity of acute dextran sulfate sodium-induced colitis in mice.…”
Section: Discussionmentioning
confidence: 99%